2019
DOI: 10.1002/jcb.29296
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally expressed long noncoding RNA B3GALT5‐AS1 may serve as a biomarker for the diagnostic and prognostic of gastric cancer

Abstract: Early diagnosis of gastric cancer (GC) is an effective method to improve prognosis. Increasing number of long noncoding RNAs (lncRNAs) have been reported as biomarkers for several cancers. We aim to detect the level of lncRNA B3GALT5‐AS1 and its association with clinical parameters and to further explore its application value in GC. We measured serum B3GALT5‐AS1 expression in 107 patients with GC, 40 polyp patients, and 87 normal controls to explore the significance of serum B3GALT5‐AS1 in GC using the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…It has been reported that the expression levels of lncRNAs AGAP2-AS1 and HOXA11-AS are signi cantly correlated with poorer prognosis and shorter OS in patients with GC, and lncRNA HOXA11-AS is tightly correlated with tumor size, TNM stage, and lymph node metastasis of GC (17,18). Previous studies have found that the expression levels of lncRNAs SNHG17 and B3GALT5-AS1 in GC tissues are signi cantly correlated with increased invasion depth, lymphatic metastasis, and advanced TNM stage (19,20). However, the expression of lncRNAs DGCR5 and ARHGAP27P1 are signi cantly downregulated in GC tissues, and its downregulation was closely associated with increased invasion depth, advanced TNM stage, and lymphatic metastasis (20,21).…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that the expression levels of lncRNAs AGAP2-AS1 and HOXA11-AS are signi cantly correlated with poorer prognosis and shorter OS in patients with GC, and lncRNA HOXA11-AS is tightly correlated with tumor size, TNM stage, and lymph node metastasis of GC (17,18). Previous studies have found that the expression levels of lncRNAs SNHG17 and B3GALT5-AS1 in GC tissues are signi cantly correlated with increased invasion depth, lymphatic metastasis, and advanced TNM stage (19,20). However, the expression of lncRNAs DGCR5 and ARHGAP27P1 are signi cantly downregulated in GC tissues, and its downregulation was closely associated with increased invasion depth, advanced TNM stage, and lymphatic metastasis (20,21).…”
Section: Discussionmentioning
confidence: 93%
“…1A ). It has been previously suggested that B3GALT5-AS1 may originate from autocrine gastric tumor cells and is closely associated with gastric tumor metastasis ( 13 ). However, the specific regulatory mechanism underlying the effect of B3GALT5-AS1 on tumor metastasis remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The moderate diagnostic value of CEA and CA199 for the early detection of gastric cancer highlights the importance and urgency of developing novel biomarkers with high specificity and sensitivity ( 30 ). It has been reported that B3GALT5-AS1 can acts as a diagnostic and prognostic biomarker of gastric cancer ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have reported that lncRNAs have great potential value in the diagnosis and treatment of GC, such as lncRNA CADM1-AS1, 31 lncRNA p4516, 16 and B3GALT5-AS1. 32 lncRNAs RP11-169F17.1 and RP11-669N7.2 are found to be novel prognostic biomarkers of GC and might play an important role in gastric disorders caused by Helicobacter pylori infection, as revealed by the bioinformatics analysis of Yang and Song. 33 Additionally, KRT19P3 was found to inhibit the proliferation and metastasis of GC by COPS7A meditating the nuclear factor κB (NF-κB) pathway.…”
Section: Discussionmentioning
confidence: 99%